P111 Quantification of active proteinase 3 in sputum samples using a novel activity-based immunoassay. (December 2018) - Ferguson, TEG; Moffitt, KL; Ramsay, D; Robb, C; McCafferty, DF; Kennedy, A; DiPetrillo, K; Walker, B
Abstract : Introduction and objectives: Proteinase 3 (Pr-3) is a serine protease secreted from neutrophils along with neutrophil elastase (NE) and cathepsin G (Cat G) in inflammatory respiratory diseases such as COPD, bronchiectasis and cystic fibrosis (CF), contributing to the inflammation and destruction of the lung matrix. There is increasing interest in these proteases as biomarkers of infection and inflammation in respiratory diseases. Here we report the use of a novel ProteaseTag ® Active Proteinase 3 Activity-Based Immunoassay (ABI) to quantify active Pr-3 in sputum samples. Methods: Expectorated sputum (n=21) was processed using 5 parts phosphate buffered saline (PBS), centrifugation at 3000 g for 30 min at 4°C, followed by aliquoting and storage of the sol supernatant at −80°C. The matrix effect was investigated by analysing 10 sputum sol samples on the Pr-3 ABI over a wide dilution range (x1–x800). Quantification of active Pr-3 in the sputum sol was carried out on the ABI following the manufacturer's instructions (ProAxsis Ltd.), diluting appropriately as indicated by the matrix investigation. Active Pr-3 was also quantified by kinetic assay using the fluorogenic substrate Abz-VADnVRDRQ-EDDnp (Peptanova) on a FLUOstar Omega plate reader (BMG Labtech) at λex =320 nm and λem =400 nm. Results: The Active ProteaseTag ® Pr-3 ABI allowed successful quantification of active Pr-3, with detection limits ranging from 7.81 ng/ml to 500 ng/ml, and did not detect NE or Cat G. An assay matrix effect was observed in the measurement of Pr-3 in sputum sol, but dilutions of x50–x400 were found to be statistically similar (p<0.05), therefore the minimum recommended dilution of sputum sol is x50. The ABI enabled quantification of active Pr-3 in 15 of the 21 sputum samples. Active Pr-3 concentrations displayed a positive correlation with levels measured by kinetic assay (r=0.97), however the kinetic assay was less sensitive requiring higher standard curve concentrations. Conclusions: We have developed an ABI which enables the specific quantification of active Pr-3 in clinically relevant sputum samples. The ABI provides an improved method for quantification of active Pr-3 levels versus other available assays and provides a new tool for researchers working in the field of neutrophilic proteases.